Survey of Wild Trees and Shrubs in Eastern Region of Libya and Their Economical Value - Farag El-Mokasabi (AlQalam Journal of Medical and Applied Sciences, 2022)
The aim of the present study was to identify the wild trees and shrubs among the diverse flora of Eastern region ecosystem that are used economically and therapeutically. Current data revealed that the total number of wild trees and shrubs surveyed in the region was 88 species, belonging to 31 families and 62 genera. Retama monosperma (L.) Boiss. subsp. bovei (Spach) Maire has been collected for the first time and it forms a new record for Libya, with the presenece of three endemic taxa Arbutus pavarii Pamp., Cupressus sempervirens L. var. horizontalis (Mill.) Gordon. and Capparis spinosa var. krugeriana. The species collected were traditionally used for medicinal and non-medicinal purposes. More than 80 medicinal uses were recorded for 46 species mentioned in the present study and 10 non-medicinal uses were also mentioned